2022
DOI: 10.3390/horticulturae8090826
|View full text |Cite
|
Sign up to set email alerts
|

Root Exploration, Initial Moisture Conditions, and Irrigation Scheduling Influence Hydration of Stratified and Non-Stratified Substrates

Abstract: Soilless substrate stratification (i.e., layering unique substrates within a single container) is an emerging substrate management strategy that may provide opportunities to augment nursery resource use. As such, this research aimed to analyze water movement through containers during hydration events under different initial moisture conditions. The results indicated substrate stratification had minimal influence on water movement compared to non-stratified systems (uniformly filled nursery containers). Cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Once plant root establishment took place, there were visually similar observed patterns to that of fallow profiles, yet fluctuations were more extreme (Figure 6). Plant roots have been shown to have large effects on water movement (Criscione, Fields, & Owen, 2022; Hoskins et al., 2014) and moisture content distributions (Bauerle et al., 2013) in soilless substrate systems. Pustjarvi and Robertson (1975) stated that in most soilless substrates, matric tensions are likely to range between −10 and −100 hPa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Once plant root establishment took place, there were visually similar observed patterns to that of fallow profiles, yet fluctuations were more extreme (Figure 6). Plant roots have been shown to have large effects on water movement (Criscione, Fields, & Owen, 2022; Hoskins et al., 2014) and moisture content distributions (Bauerle et al., 2013) in soilless substrate systems. Pustjarvi and Robertson (1975) stated that in most soilless substrates, matric tensions are likely to range between −10 and −100 hPa.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the tortious pathways for water movement slows down infiltration rates, and as a result, more thorough wettings are typically achieved (Bilderback & Jones, 2001). Criscione, Fields, and Owen (2022) reported that water infiltrated (entry‐to‐exit) more slowly through the entire container profile in stratified substrates compared to non‐stratified systems. Therefore, infiltrating water velocities were likely slower in the top half (with regard to traditional systems; Hoskins et al., 2014), equaling a more laterally distributed wetting front ( r = 0.8038).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential use of stratified substrates has been shown to improve natural resource efficiency by modifying the physical nature of the container-substrate profile (Fields et al 2021b). Preceding stratified research has layered fine-textured substrates (e.g., to enhance water and mineral nutrient retention) in the upper container proportions, whereas in the lower proportions, coarse substrates were used to encourage drainage and reduce deleterious water table effects (Criscione et al 2022a(Criscione et al , 2022bFields et al 2021b). Promising results have demonstrated that substrate stratification may support possibilities for nursery growers to reduce water and fertilizer inputs by 25% and 20%, respectively, and continue producing equivalent or better crops than traditionally used nursery production methods (Criscione et al 2022a;Fields et al 2021b).…”
mentioning
confidence: 99%